STUDY OF CHANGES IN BIOLOGICAL AND HEAMOTOLOGICAL MARKERS IN PAKISTANI PATIENTS OF AGES ABOVE 50 YEARS WITH CHRONIC HEPATITIS C GENOTYPES 1-5 IN THE ERA OF DIRECT ACTING ANTIVIRAL DRUGS - Kashif Waqas; Syed Zeeshan Haider Naqvi; Usama Basirat; Muhammad Usama Arshad; Javed Anver Qureshi; Sabira Sultana; Faheem Hadi (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
The Hepatitis C virus is RNA containing virus which damages liver at molecular level and causes inflammatory conditions such as fibrosis and cirrhosis and can also lead to cancer. Various direct-acting anti-viral drugs available in local area were administered to patients. These drugs work on principle by targeting specific proteins which damage the virus. Many drugs are administered in combination and produce a sustained virological response in 12 weeks. A follow-up research was performed to evaluate 3 months of treatment outcome of some direct-acting antiviral drugs in 131 patients (110 patients of HCV genotype 3) above 50 years using relevant biological parameters. 115 patients yielded a pooled SVR of more than 85% after twelve weeks of commonly used antiviral drug evaluation. Commonly used antiviral drugs in Sialkot, Pakistan, showed effectiveness in HCV patients having genotypes 1-5 as evidenced by biological and haemotological markers.